Parâmetros de estresse oxidativo e estudo de lesõs histopatológicas em jundiás (Rhamdia quelen) expostos a agroquímicos - Ferreira, Daiane (2010)
Due to the proximity of crop and fish culture areas, some agrichemicals that could be harmful for fish could enter into fishponds by different ways, such as by leaching through rain. The contamination of the aquatic environment by pesticides is a problem of global importance because of its toxic effects on non-target organisms. These products may affect toxicological endpoints in fish. Among the effects that pesticides can cause fish is the formation of reactive oxygen species (ROS) and changes in antioxidant enzymatic and nonenzyme, which may show a situation of oxidative stress. The formation of ROS may be associated with different pathological processes in fish exposed to pollutants such as pesticides. Several biochemical and physiological responses occur when a pesticide enters the body, resulting in the adaptation of the organism to the contaminant or if the body can not efficiently metabolize these products, they may induce toxicity. Rhamdia quelen (Teleostei) were exposed to sub-lethal concentrations of methyl parathion (MP), a glyphosate based herbicide (Gly), and tebuconazole (Teb). The liver of R. quelen exposed to MP and Teb showed enhanced levels of thiobarbituric acid reactive substances (TBARS), compared to the control fish (56% and 59%, respectively). In contrast, Gly did not alter the TBARS generation. The protein carbonyl content increased only in fish exposed to Teb. Fish exposed to the three agrichemicals showed a significant decrease of catalase activity (52%, 48%, and 67%, respectively) and increased glutathione-S-transferase (57%, 46%, and 160%, respectively) activity. Fish exposed to MP, Gly, and Teb showed higher reduced glutathione (151%, 472%, and 130%, respectively, when compared to the control levels) and ascorbic acid concentrations (121%,102%, and 184%, respectively),while the non-protein thiol content increased only in R. quelen exposed to tebuconazole. Fish exposed to MP and Teb showed several pathological changes in the liver, including hepatocyte degeneration and bile stagnation. The present work reports for the first time the toxicity of the pesticide MP and the fungicide Teb in R. quelen, and as in other works, suggests the relatively lower liver toxicity of Gly for fish. The data presented herein demonstrate that sublethal concentrations of MP and Teb cause changes in oxidative stress parameters as well as hepatic cell injuries in R. quelen, and that these parameters have the potential to be developed as bioindicators of exposure to these agrichemicals.